Eyewitness question & answer book - Farndon, John. (London ; New York : Dorling Kindersley, 1993)
A quiz book featuring over 250 questions on nature, history, science, and technology to stimulate learning about the world around us.
Includes index.
Keywords: Children's questions and answers; Curiosities and wonders -- Juvenile literature; Curiosities and wonders; Questions and answers